Compressibility characteristics of Eucheuma cottonii L. powder prepared using microcrystalline cellulose and kappa-carageenan as binders - Zainal Abidin, Zafirah (2011)
This thesis presents the study of compressibility characteristics of Eucheuma cottonii powder prepared with different binders and methods of compression. Eucheuma cottonii is red seaweed that has been cultivated in many tropical countries including Malaysia. This study consists of two different tabletting processes which were tabletting of Eucheuma cottonii with microcrystalline cellulose as a binder using direct compression method and the tabletting of Eucheuma cottonii with kappa-carrageenan as a binder using a modified wet granulation method. Seaweed has shown potential as anti-obesity, hypocholesterol, antioxidant and organ protective properties on cardiovascular health. A commercial universal testing machine with a 13-mm cylindrical stainless steel uniaxial die has been used in this study for the compression of powder. Seven different compositions of binder ranging from 0% (w/w) to 100% (w/w) with two different amounts of feed powders, 0.5g and 1.0g have been prepared. Pressures within the range of 7.5 to 74 MPa have been used during the compression process. A constant compression speed of 5 mm min-1 has been applied throughout the compression process. Effect of different amounts of feed powders and composition of binders on compression characteristics has been studied. Relationship such as volume-pressure, densitypressure, ejection force-force and tensile strength-pressure were represented in order to study the compression characteristics of Eucheuma cottonii. To understand the result further, three compression equations were used, Kawakita and Lüdde, Heckel and Walker. The best tablet formulation for both tabletting processes was determined. For tabletting of Eucheuma cottonii with microcrystalline cellulose, it has been determined that tablet with 70% microcrystalline cellulose as a binder is the best formulation whereas for the tabletting of Eucheuma cottonii with kappa-carrageenan as a binder,tablet which the composition containing 10% kappa-carrageenan as a binder has been the best formulation. Based on this approach, a better understanding of the compressibility characteristics of Eucheuma cottonii is obtained which is essential for the enhancement of the tabletting industry in Malaysia.